Popular urbanization in Asuncion, Paraguay - Canese de Estigarribia, Marta Isabel (Revista INVI, 2019)
This paper analyzes the processes of urbanization, organization and resistance taking place in urban areas developed through popular intervention in Asuncion, Paraguay. To this end, this study collected data from official institutions and conducted qualitative research through observation and in-depth interviews with 30 local community leaders. According to those surveyed, the popular urbanization process dates back to the colonial period, focusing on the riverside area of Asuncion, then expanded to other municipalities within the metropolitan region of the city. Local communities built these popular neighborhoods through the elaboration of organizational networks and solidarity initiatives. While mechanisms of occupation and resistance included street mobilization, community organizations still rely on institutional management to achieve better citizen participation.